Study on the Synergistic Extraction of Lithium from Spent Lithium Cobalt Oxide Batteries by Molten Salt Electrolysis and Two-Step Precipitation Method - Hui Li; Haotian Li; Jinglong Liang; Hongyan Yan; Zongying Cai (Crystals, 2021)
With the continuous development of society, the number of spent lithium-ion batteries has also increased, and the recovery of valuable metals such as Ni, Co, and Li has become the main research direction of many scholars. In this paper, the extraction process of lithium that enters the molten salt after LiCoO2 electrolysis is studied. Oxalic acid and phosphate are added to molten salt containing lithium ions to realize the two-part precipitation method to extract lithium. The influence of pH value, temperature, reaction time, and oxalic acid (or phosphate) addition on the process of oxalic acid calcium removal and phosphate lithium precipitation is analyzed. The results show that the calcium removal rate of oxalic acid has reached 99.72% (Initial conditions: PH = 7.0, T = 70 °C, t = 1.5 h, n(H2C2O4):n(Ca2+) = 1.2:1). The precipitation of Li3PO4 obtained in the phosphate extraction experiment of lithium is as high as 88.44% (Initial conditions: PH = 8.0, T = 70 °C, t = 1.5 h, n(actual dosage of Na3PO4):n(theoretical dosage of Na3PO4) = 1.2:1). The obtained lithium phosphate crystals show regular spherical particles, which can be seen by SEM.